2017
DOI: 10.1080/13557858.2017.1379598
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the special need for protection of vulnerable refugees: testing the applicability of a screening method (RHS-15) to detect traumatic disorders in a refugee sample in Germany

Abstract: The RHS-15 seems to be practicable, economical, and rapidly deployable for the widespread detection of traumatic disorders in refugees living in Europe. The tool proved useful to aid diagnostic assessments and provide treatment to individuals in need, however the time of examination (resp. the duration of staying in the target land) influences the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Within a German refugee sample, the different language versions of the RHS-15 showed excellent internal consistencies with Cronbach's a ranging from .91 to .93, and good convergent and predictive validity (41). The practicability and efficiency of the RHS-15 have been demonstrated in previous studies (39).…”
Section: Methodsmentioning
confidence: 66%
See 3 more Smart Citations
“…Within a German refugee sample, the different language versions of the RHS-15 showed excellent internal consistencies with Cronbach's a ranging from .91 to .93, and good convergent and predictive validity (41). The practicability and efficiency of the RHS-15 have been demonstrated in previous studies (39).…”
Section: Methodsmentioning
confidence: 66%
“…Another potential bias could be the stage and long-term perspective of the individual asylum procedures. An earlier study conducted by our group demonstrated that the results of the RHS-15 were different between refugee groups immediately after arrival compared to those with a longer duration of residence in the country (39). Moreover, in the present study primarily factors that increased vulnerability were examined.…”
Section: Limitationsmentioning
confidence: 66%
See 2 more Smart Citations
“…It is an efficient self-rating instrument which assesses emotional distress in refugees, thereby comprising symptoms of PTSD, depression, and anxiety. The 13-item version shows good psychometric properties in refugee samples in the US and in Germany, comparable to the characteristics of the RHS-15 ( 8 , 9 , 33 ). Cronbach's α varied between 0.89 and 0.95 for the 12 time points.…”
Section: Methodsmentioning
confidence: 73%